Factors Affecting The Profitability Of Property And Real Estate Companies In Indonesia - Tri Wahyuningsih; Veni Soraya Dewi; Betari Maharani (Universitas Tidar, 2023)
Profitability is the company's ability to generate profits by using owned sources such as assets, capital or company sales. This study aims to determine the effect of working capital, sales growth, debt, company size and company growth on profitability. The research data used is data on the financial statements of property and real estate companies listed on the Indonesia Stock Exchange from 2016 to 2020. The sampling method uses purposive sampling, which is to obtain samples according to certain criteria. The total sample is 38 property and real estate companies. Hypothesis testing in this study using multiple linear regression analysis with the help of SPSS version 25.0 program. The test results show that working capital, company growth, firm size and company growth have a positive effect on profitability, while debt has no effect on profitability.